2007
DOI: 10.1111/j.1742-1241.2007.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk management and its impact in Australian general practice patients with type 2 diabetes in urban and rural areas

Abstract: Despite a number of national initiatives to improve general practice care and specifically support better care in rural areas, cardiovascular risk management and its impact in Australian general practice patients with type 2 diabetes was still suboptimal during the study period especially among patients from rural areas. Greater effort will be required to reduce the disparity in risk factor prevention for CVD between urban and rural people with type 2 diabetes in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
0
20
0
3
Order By: Relevance
“…The included studies were published over a 21-year time span (1990 to 2011) and had quality scores based on the STROBE checklist that ranged from 8.5 to 21 (median 17.5) out of a total of 22 possible items (0.5 points given for partial reporting). Two reports provided data on the same study [44,48], and six studies included data for more than one patient cohort [43,49,54,66,71,72]. Thus, 58 patient populations (or cohorts) were included in our study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were published over a 21-year time span (1990 to 2011) and had quality scores based on the STROBE checklist that ranged from 8.5 to 21 (median 17.5) out of a total of 22 possible items (0.5 points given for partial reporting). Two reports provided data on the same study [44,48], and six studies included data for more than one patient cohort [43,49,54,66,71,72]. Thus, 58 patient populations (or cohorts) were included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Exploring rural–urban differences was the primary objective of 18 studies (35%) [2,27,28,30,31,35,36,39,43,44,49,51,54,59,68,69,71,73]. Seven studies reported medication adherence (the proportion of doses taken as prescribed over a specific time period) or persistence (the length of continuous treatment) [76], and 47 reported outcomes related to medication utilization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations